2019
DOI: 10.3390/v11020158
|View full text |Cite
|
Sign up to set email alerts
|

THO Complex Subunit 7 Homolog Negatively Regulates Cellular Antiviral Response against RNA Viruses by Targeting TBK1

Abstract: RNA virus invasion induces a cytosolic RIG-I-like receptor (RLR) signaling pathway by promoting assembly of the Mitochondrial antiviral-signaling protein (MAVS) signalosome and triggers the rapid production of type I interferons (IFNs) and proinflammatory cytokines. During this process, the pivotal kinase TANK binding kinase 1 (TBK1) is recruited to the MAVS signalosome to transduce a robust innate antiviral immune response by phosphorylating transcription factors interferon regulatory factor 3 (IRF3) and nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…It has been reported that TBK1 activity can be regulated by kinase activity modulation, posttranslational modification such as phosphorylation or ubiquitination, as well as prevention of functional TBK1-containing complex formation ( 37 , 38 ). It was reported that NLRP4-DTX4, TRIP Siglec1-TRIM27, THOC7, and TRAF3IP3 promote K48-linked polyubiquitination of TBK1 ( 19 , 34 , 39 , 40 ). Although many inhibitors were found or patented, there is still much to be understood by searching more interaction partners of TBK1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TBK1 activity can be regulated by kinase activity modulation, posttranslational modification such as phosphorylation or ubiquitination, as well as prevention of functional TBK1-containing complex formation ( 37 , 38 ). It was reported that NLRP4-DTX4, TRIP Siglec1-TRIM27, THOC7, and TRAF3IP3 promote K48-linked polyubiquitination of TBK1 ( 19 , 34 , 39 , 40 ). Although many inhibitors were found or patented, there is still much to be understood by searching more interaction partners of TBK1.…”
Section: Discussionmentioning
confidence: 99%
“… Signaling molecule Classification Regulator Function Ref. TBK1 PTMs Positive MIB K63-linked ubiquitination 161 TBK1 K63-linked ubiquitination 154 Nrdp1 K63-linked ubiquitination 163 RNF128 K63-linked ubiquitination 162 USP1–UAF1 complex Deubiquitination 164 UBQLN2 Phosphorylation 159 Src Autophosphorylation 160 TBK1 Autophosphorylation 155 RKIP Autophosphorylation 158 GSK3β Self-association and autophosphorylation 157 Dnmt3a Recruitment of HDAC9 for deacetylation 165 HDAC3 Deacetylation 166 TRIM9 Recruitment of GSK3β for activation 157 Negative ASB8 K48-linked ubiquitination 172 USP38 K48-linked ubiquitination 176 DYRK2 K48-linked ubiquitination 174 THOC7 K48-linked ubiquitination 175 TRIP K48-linked ubiquitination 173 Siglec1 Recru...…”
Section: Role Of Ptms In Regulating Signal Transductionmentioning
confidence: 99%
“…In contrast, several TBK1-regulating proteins negatively impact TBK1. K48-linked polyubiquitination of TBK1 induced by E3 ubiquitin ligases such as SOCS box-containing 8 (ASB8) 172 , TRAF-interacting protein 173 , dual-specificity tyrosine phosphorylation-regulated kinase 2 (DYRK2) 174 , and THO complex subunit 7 homolog (THOC7) 175 triggers proteasomal degradation of TBK1 and ultimately terminates immune activation. Interestingly, USP38 permits K48-linked ubiquitination and subsequent degradation of TBK1 by specifically removing K33-linked ubiquitin chains from the same lysine site on TBK1 176 .…”
Section: Regulation Of Tbk1 By Host Factorsmentioning
confidence: 99%
“…We did identify a number of other proteins with heavy labelled peptides in CCM from three or more conceptuses, with light labelled versions of these proteins also identified in the CCM from other conceptuses ( Table 3) included THO complex subunit 7 homolog, THOC7. Interestingly, THOC7 has been suggested to negatively regulate type I IFN production [50]. Another protein present in the media from five conceptuses (heavy labelled in CCM from three conceptuses) is GPRC5A.…”
Section: De Novo Synthesised Proteins In Conceptus-conditioned Mediamentioning
confidence: 99%